Cross-cultural applicability of the Inventory of Problems–29 (IOP–29): a pre-registered German replication of Akca, Tepedelen, et al. (2023) - Höpfner, Henrike; Uysal, Burcu; Stemmler, Mark; Akca, Ali Y.E.; Giromini, Luciano (Psychiatry Psychology and Law, 2025)
Assessing the credibility of psychological problems in forensic evaluations is crucial. The Inventory of Problems–29 (IOP–29) is becoming a valuable symptom validity test (SVT) worldwide and has been validated in over 15 languages. This study evaluates the German IOP–29 and fills a gap by replicating a study of Akca, Tepedelen, et al. We analysed 384 IOP–29 protocols from 128 German-speaking adults (range = 18–87 years) under three conditions: honest, random and feigned responses (post-traumatic stress disorder, PTSD; depression; schizophrenia). Statistical analyses showed that the False Disorder Probability Score (FDS) effectively discriminated between honest and feigned responses (Hedges g = 3.90), with a sensitivity of.91 and a specificity of.95 at an FDS cut-off value of ≥.50. A new index for detecting careless or random responses also showed promising results. This study confirms the utility of the IOP–29 in the German-speaking population and supports its cross-cultural applicability.
CRIS-Team Scopus Importer:2025-01-31
Keywords: depression; feigning; German; IOP–29; malingering; PTSD; schizophrenia; symptom validity test